PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN KFC INDONESIA - Zalvani, Muhammad Hazza; Ilham, Fauzhan; Nugraha, Tegar adi; Wicaksono, Magribi Arif (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of organizational culture and organizational commitment on employee performance at KFC Indonesia, a leading global fast-food company. In this context, organizational culture encompasses the values, norms, and practices shaping workplace interactions, while organizational commitment refers to employees' emotional attachment and dedication to company objectives. A quantitative approach was employed, involving a survey of 100 active KFC Indonesia employees. Multiple regression analysis was applied to examine the relationship between the independent variables (organizational culture and commitment) and the dependent variable (employee performance). The findings indicate that organizational culture significantly contributes to enhancing employee performance by fostering an environment conducive to innovation and collaboration. Meanwhile, organizational commitment exerts a greater influence than culture, underscoring the importance of emotional attachment, loyalty, and a sense of belonging among employees. This research offers strategic recommendations to strengthen both factors to achieve optimal organizational performance in the competitive fast-food industry.